Chemical composition and in vitro rumen fermentation characteristics of various tropical seaweeds - Hidayah, Nur; Noviandi, Cuk Tri; Astuti, Andriyani; Kustantinah, Kustantinah (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: This research aimed to evaluate potential tropical seaweed from Indonesia as an ingredient or supplement feed for ruminants based on chemical composition and in vitro rumen fermentation parameters. Materials and Methods: The seven natural tropical seaweeds (three green and four red species) were collected from Ndrini and Sepanjang Beach, Gunungkidul, Yogyakarta, Indonesia. The experimental design on secondary metabolite profiles used a completely randomized design, and the in vitro gas production test used a randomized complete block design with seven seaweed species variances and four replications (blocks) based on rumen fluid collection time. The data obtained was analyzed using analysis of variance (ANOVA), and Duncan‘s Multiple Range Test was used to test the variation in the analysis. Results: The seven tropical seaweed species have potential as mineral sources for ruminants, except for macromineral (P and S) and micromineral (Cu). The red tropical seaweed has potential as a protein source (Gelidium spinosum (S.G.Gmelin) P.C. Silva, Hypnea pannosa, and Acanthopora muscoides (L.) Bory), and the green seaweed (Chaetomorpha linum (O.F. Mull.) Kutz and Cladopora sp.) has potential as a crude fiber (CF) source for ruminants. As indicated by secondary metabolites and gas production in vitro, the green species (C. linum (O.F. Mull.) Kutz and Enteromorpha compressa) and red species (A. muscoides (L.) Bory and Gelidium amansii (J.V. Lamouroux) J.V. Lamouroux) could be degraded in the rumen and had quite high phenolic compounds. Conclusion: The seven tropical seaweed species have the potential to be an ingredient or supplement feed for ruminants, and there were four species that have the potential to reduce methane emissions. J. Adv. Vet. Anim. Res., 10(4): 751–762, December 2023 http://doi.org/10.5455/javar.2023.j731